The Effectiveness of Blended Learning on Learning Interests and Outcomes at SDN 1 Labuhan Sreseh Sampang - Didik Purwandika; Muhajir Muhajir; Nuril Huda (International Forum of Researchers and Lecturers, 2025)
This study explores the effectiveness of the implementation of blended learning at SDN 1 Labuhan Sreseh Sampang, with a focus on increasing students' interest and learning outcomes. Blended learning, which combines face-to-face and online learning methods, provides greater flexibility and accessibility, which has the potential to increase student engagement and participation in the learning process. Quantitative methods were used in this study to collect data from 45 students through questionnaires designed to measure interest and learning outcomes. The results of the analysis showed that the application of blended learning had a significant positive effect on increasing students' interest and learning outcomes. These findings confirm that blended learning can be an effective approach to improve the quality of education at the primary school level, especially in the face of the challenges of the digital era and technological advances in education.